Assessing Mitigation Translocation as a Tool to Reduce Human–great Horned owl Conflicts. - Washburn, Brian E.; Massey, Benjamin J.; Sonnek, Alec C.; Pitlik, Todd J. (Environmental Management, 2025)
The great horned owl (Bubo virginianus) is a generalist predator that inhabits wide-ranging territories that are relatively stable throughout the year. These owls are also involved in a variety of human–owl conflicts, including killing of domestic poultry, predating colonially nesting seabirds and shorebirds, and pose a hazard to safe aircraft operations. Managing these conflict situations presents unique challenges as great horned owls are nocturnally active and occupy a wide range of habitats. We evaluated information about great horned owl collisions with civilian aircraft and found this is a contemporary and growing aviation safety issue. We conducted a study to determine whether a biological (e.g., age of the bird) and logistical factors (e.g., month and translocation distance) influenced the return rate of great horned owls following a mitigation translocation from 13 civil airports and three military airfields during 2013–2023. Great horned owls (n = 1,020) were live-captured, banded, and translocated various distances from the airfields which were then monitored for returning owls. We developed a set of candidate binomial-distributed generalized linear models [involving all possible subsets of three factors (age, month, and distance translocated) as well as interactions]. The return rate of translocated great horned owls was very low (i.e., 2.6%) and we found no evidence that these biological and logistical factors influenced great horned owl homing behavior. Management programs that use release sites 40 km from the conflict location and translocate individual owls only once would increase program efficacy by minimizing homing behavior and decreasing implementation costs.